High‐Definition Transcranial Direct Current Stimulation Enhances Exercise‐Induced Hypoalgesia in Healthy Individuals: An fNIRS Study - Ruihan Wan; Haozhi Zhao; Xue Jiang; Beibei Feng; Yafei Wang; Chen Gong; Yangyang Lin; Wangwang Yan; Yixuan Ku; Yuling Wang (Brain and Behavior)
ABSTRACT Background This study investigates whether anodal high‐definition transcranial direct current stimulation (HD‐tDCS) enhances exercise‐induced hypoalgesia (EIH) and explores brain plasticity changes using functional near‐infrared spectroscopy (fNIRS). Methods Thirty‐nine participants were randomly assigned to either the active (n = 19) or sham HD‐tDCS (n = 20) group. Both groups performed 25 min of moderate‐intensity aerobic exercise followed by 20 min of either active or sham HD‐tDCS applied to the left primary motor cortex (M1). Primary outcome: pressure pain threshold (PPT) at a local site. Secondary outcomes: PPT at a remote site, cold pain threshold (CPT), and brain activation changes via fNIRS during the cold pressor test. Results Both groups showed significant increases in PPTleg (active: from 42.21 ± 11.77 N to 51.29 ± 12.75 N; sham: from 41.41 ± 9.73 N to 45.29 ± 12.05 N, p < 0.001) and PPTforearm (active: from 31.69 ± 6.06 N to 36.99 ± 6.35 N; sham: from 32.66 ± 7.34 N to 37.08 ± 10.56 N, p < 0.001). The active group showed a significantly greater increase in PPTleg compared to the sham group (9.08 ± 8.01 N vs. 3.69 ± 4.36 N, p < 0.012). fNIRS analysis revealed significant changes in specific cortical channels in the active group (p < 0.05), with a negative correlation between cortical activation in CH16 and PPTleg (r = −0.405, p = 0.011). Conclusion HD‐tDCS over M1 enhances EIH and is associated with increased brain activation in sensory‐motor processing areas. Trial Registration Clinical trial registration: ChiCTR2100048146